2001
DOI: 10.3146/i0095-3679-28-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Distribution of Genetic Diversity in Arachis hypogaea

Abstract: The U.S. maintains a large (> 8000 accessions) and genetically diverse collection of peanut (Arachis hypogaea L.) germplasm. It is costly to screen all accessions within this collection for traits that could be useful in cultivar development. The objective of this research was to identify countries of origin that are rich sources of resistance to important peanut diseases. This would allow peanut breeders to focus their efforts on smaller subsets of the germplasm collection. Accessions in the peanut cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Use of this mini core collection would not have significantly improved the efficiency of identifying resistance to the peanut root‐knot nematode in the core collection (Table 4) This was unexpected since we had previously demonstrated that some geographical areas are rich sources of resistance to the peanut root‐knot nematode (Holbrook et al, 2000a; Holbrook and Isleib, 2001) and shown that the clusters used to develop the core collection improved the efficiency of identifying nematode resistance in the entire collection (Holbrook et al, 2000b). An examination of the mean data for accessions showed similar grouping in the clusters used to select this core of the core collection.…”
Section: Resultsmentioning
confidence: 98%
“…Use of this mini core collection would not have significantly improved the efficiency of identifying resistance to the peanut root‐knot nematode in the core collection (Table 4) This was unexpected since we had previously demonstrated that some geographical areas are rich sources of resistance to the peanut root‐knot nematode (Holbrook et al, 2000a; Holbrook and Isleib, 2001) and shown that the clusters used to develop the core collection improved the efficiency of identifying nematode resistance in the entire collection (Holbrook et al, 2000b). An examination of the mean data for accessions showed similar grouping in the clusters used to select this core of the core collection.…”
Section: Resultsmentioning
confidence: 98%
“…Core (representing 10% of total collection) and mini-core (representing 10% of core collection) collections were made for the groundnut genetic resources available in USDA/ARS (Holbrook et al, 1993; Holbrook and Dong, 2005), ICRISAT (Upadhyaya et al, 2002, 2003), and China (Jiang et al, 2008, 2010). Holbrook and Isleib (2001) observed that the resistance genes were cluster geographically and accessions with multiple disease resistance were most common in India, Mozambique, and Senegal.…”
Section: Groundnut Improvement Using Conventional Approachesmentioning
confidence: 99%
“…This germplasm collection has served as a valuable source of diversity for resistance to many pathogens of peanut (Holbrook and Isleib, 2001). However, it is not feasible to evaluate this collection, in its entirety, for resistance to PAC using currently available screening techniques.…”
Section: Screening For Sources Of Resistancementioning
confidence: 99%